KUALITAS DADIH SUSU KERBAU DENGAN LAMA PEMERAMAN YANG BERBEDA - Evi Daswati; Hidayati dan; , Elfawati (Jurnal Peternakan, 2009)
An experiment wasjconducted to determine quality of dadih from buffalo milk with different incubation time. They were randomly allocated into 4 treatments in a randomized block design with 3 replications. Treatments were: A = 12 hours B =24 hours C =36 hours and D =48 hours. The result of this research was showed that 48 hours the best of incubation time at temperature 450 C, which nutrient content of dadih was crude protein 9.96"', fat 9.89"', moisture 73.02%, pH value 5.02 and total plate count 1.70 x 1()6 CFU / gram.